Enantioselective comprehensive two‐dimensional gas chromatography. A route to elucidate the authenticity and origin of Rosa damascena Miller essential oils. Issue 19 (October 2015) - Krupčík, Ján; Gorovenko, Roman; Špánik, Ivan; Sandra, Pat; Armstrong, Daniel W
<x xml:space="preserve">Abstract</x> The analysis of Bulgarian and Turkish Rosa damascena Miller essential oils was performed by flow‐modulated comprehensive two‐dimensional gas chromatography using simultaneous detection of the second column effluent by flame ionization and quadrupole mass spectrometric detection. Enantioselective separations were obtained by running the samples on 2, 3‐di‐O‐ethyl‐6‐O‐tert‐butyldimethylsilyl‐β‐cyclodextrin column as the first column and on polyethylene glycol as the second column. The determination of enantiomeric or diastereomeric excess of some terpenoic solutes is a possible route for quality or authenticity control as well as for the elucidation of the country of origin.